Prevention Of Polyandry In The Perspective Of Islamic Law And Law No. 1 Year 2023 - Maswandi, Maswandi (Legalpreneur Journal, 2026)
Marriage as a normatively protected and religious institution in Indonesia still faces the threat of polyandry practices that are contrary to moral values, religion, and applicable legal regulations. This study aims to examine the Prohibition of polyandry from the point of view of Islamic law and the construction of criminal sanctions in Law Number 1 of 2023 concerning the Criminal Code, as well as formulating an integrative prevention model. The method used is normative juridical approach through the study of literature with descriptive-analytical analysis. The results showed that all schools of jurisprudence have agreed by ijma ' ban polyandry because it is contrary to maqashid al-Sharia, especially the principle of hifzh Al-nasl and hifzh al-'irdh. Indonesia's positive law also prohibits the practice through the principle of monogamy and the provision of double marriage. The meeting point between the two legal systems is an important foundation in building a comprehensive prevention mechanism. The Integrative prevention Model includes institutional synergies between KUA, MUI, and law enforcement officials, strengthening premarital education, and digitizing national marriage records in order to realize equitable family resilience.